Bibliometric analysis of review on picture book creation methods in the chinese context based on CNKI database - Mohd Noor, Mohd Zairul; Jin, Deran; Abdulkareem Salih, Sarah (Human Resource Management Academic Research Society (HRMARS), 2024)
In the current context of Chinese picture book creation, a large number of picture book creators have emerged, but there is a significant gap in the literature review of research on Chinese picture book creation. Based on the CNKI database, this article uses a bibliometric approach to fill the gap in the literature review of Chinese picture book creation. The article provides a review of research on the creation of illustrated books in China. Through the method of review by keyword metric analysis, the research hotspots and research topics in the field of picture book creation research are elucidated. The results of the study reveal several major areas of concern to researchers of picture book creation in China. As a specific discipline of design and creativity, a review of the ways and means of creating picture books is particularly important.